2017
DOI: 10.1016/j.ijpam.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of microbial growth in urine cultures in a pediatric hematology/oncology unit over a one-year period

Abstract: BackgroundUrinary tract infections (UTIs) may present with nonspecific symptoms and without any definitive clinical signs other than fever, hence may be missed without a routine urine analysis. We retrospectively evaluated all cases of culture-positive urine infections in pediatric oncology patients in our center during the year 2015.MethodsWe assessed all positive urine culture incidents for pediatric patients receiving treatment and/or follow-up at our center during 2015. Analysis was performed on patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…[22] Nevertheless, other studies reported higher rates of documented UTI (18.5% to 47.0%) in FN patients without signs or symptoms suggestive of UTI. [13,23] As a matter of fact, in one of those studies, only 2.2% of the patients presented with urinary symptoms, and none of those had signifi cant bacteriuria. [13] Herein, we conclude that the incidence of UTI in adult cancer patients with FN is low due to a constellation of factors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[22] Nevertheless, other studies reported higher rates of documented UTI (18.5% to 47.0%) in FN patients without signs or symptoms suggestive of UTI. [13,23] As a matter of fact, in one of those studies, only 2.2% of the patients presented with urinary symptoms, and none of those had signifi cant bacteriuria. [13] Herein, we conclude that the incidence of UTI in adult cancer patients with FN is low due to a constellation of factors.…”
Section: Discussionmentioning
confidence: 96%
“…[22] The rates reported in our study are similar to those of a study on pediatric oncology patients with confirmed UTI, where 69% of UA samples were abnormal, and 85% had an absolute neutrophil count (ANC) >500 cells/mm 3 . [23] These diff erences in the presence of a UA abnormality may be attributed to the severity of neutropenia as well as the urine collection technique; a higher ANC and bladder catheterization are signifi cantly associated with the presence of pyuria. [18] Moreover, in healthy patients, a negative UA result generally has a high negative predictive value (NPV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CoNS have been isolated from bovine samples and samples from sheep with mastitis [56][57][58][59][60][61][62][63] , the hands and mobile phones of university students 33 , air samples 138,139 and health care workers' uniforms in ICUs 140 . The most common CoNS species isolated from clinical samples in Jordan were S. epidermidis and S. haemolyticus 141 , and these were isolated from neonates with septicaemia 92,93,[142][143][144] , nosocomial septic arthritis patients 114 , cancer patients with bacteremia and febrile neutropenia 97,145 , patients with bloodstream infections 132,141 , patients with nosocomial infections 100 , patients with UTIs 102,104,106,107,[146][147][148] , patients with otitis externa 110 , children with bacterial infections following autologous hematopiotic stem cell transplantation 149 , patients with surgical site infections following coronary artery bypass graft surgery 150 , and patients with endocarditis 115 .…”
Section: Staphylococcusmentioning
confidence: 99%
“…Enterococci were isolated form different clinical samples 12 , bacteremia in children 89 , bloodstream infections 79,132 , chemotherapy-induced febrile neutropenia with positive blood cultures 97 , bacterial infections in the first 90 days of life 178 , skin and soft tissue infections from ICU patients 85 , wound infections 82 , bile infections 99 , and nosocomial infections 100 . It was rarely isolated from UTIs 101,102,104,106,107,[146][147][148]160,177,[190][191][192][193] , dental diseases, 185 , sinusitis and orbital cellulitis 122 , combat-related traumatic chronic osteomyelitis 124 , and autologous hematopoietic stem cell transplantation in children 149 . E. faecalis was the most frequent isolate followed by E. faecium 100,189 .…”
Section: Enterococcusmentioning
confidence: 99%